2009
DOI: 10.1007/bf03405492
|View full text |Cite
|
Sign up to set email alerts
|

Location Restrictions on Smoking: Assessing their Differential Impacts and Consequences in the Workplace

Abstract: Objectives:To analyze existing evidence on the impact of two types of location restrictions on smoking: workplace bans and bans in hospitality settings, and to assess the extent to which they differentially affect subpopulations.Methods: A review of international studies on location restrictions on smoking published between 1990-2007.Results: Although workplace smoking bans reduce exposure to second-hand smoke (SHS) at work, their effects on overall cigarette consumption and smoking prevalence may be uneven ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Although smoke-free laws are effective in reducing community smoking rates, college student drinkers in this study reported that living within the larger smoke-free community did not affect their motivation to quit smoking or alcohol-related social behaviors. Bell and colleagues (2009) found smoke-free laws may have less impact on subpopulations such as low-income groups; others report similar findings about low-income girls and women (Greaves & Hemsing, 2009). College students may represent another subpopulation in which smoke-free laws alone do not influence alcohol- or tobacco-related behaviors.…”
Section: Discussionmentioning
confidence: 79%
“…Although smoke-free laws are effective in reducing community smoking rates, college student drinkers in this study reported that living within the larger smoke-free community did not affect their motivation to quit smoking or alcohol-related social behaviors. Bell and colleagues (2009) found smoke-free laws may have less impact on subpopulations such as low-income groups; others report similar findings about low-income girls and women (Greaves & Hemsing, 2009). College students may represent another subpopulation in which smoke-free laws alone do not influence alcohol- or tobacco-related behaviors.…”
Section: Discussionmentioning
confidence: 79%
“…425 Some limited evidence suggests that the effects of smoke-free workplace policies may be larger in men than in women and among persons with greater education, but favorable effects were generally seen in all groups studied. 426432 …”
Section: Resultsmentioning
confidence: 99%
“…Another emerging issue involves the inequality aspect of the smoke-free policy, focusing on its impacts on less powerful subpopulations, particularly women of low socioeconomic status 10 11. In California, low-income women were found to be more likely to be exposed to SHS at work in a smoke-free community without uniform adherence to smoke-free rules 12.…”
Section: Introductionmentioning
confidence: 99%